Assessment of Toxic Metals in Groundwater at Residential Area nearby Industrial Areas: Assessment of Heavy Metal Contamination in Groundwater near Industrial Areas (Journal of Advances and Scholarly Researches in Allied Education, 2021)
At present, environmental protection is the main need of the society6. The industrial effluents cause soil and groundwater pollution besides causing a number of adverse effects on agriculture producer, animals and health of people living in the neighboring areas since it contains waste chemicals and toxic heavy metals. Heavy metals are readily mobile in environment and accumulate in flora and fauna. Excessive levels of ionic metals in groundwater have detrimental health risk to humans and posed environment stresses. Heavy metals contamination has been recognized as a major environmental concern due to their pervasiveness and persistence. These heavy metals are not biodegradable hence the need to develop a remediation technique that efficient, economical and rapidly deployable in a wide range of physical settings. Results obtained exhibited that As, Cd, Cr, Fe, Mn Pb were not found in any studied groundwater samples whilst Cu (0.00 – 0.25 mgL) found only in sample G2 Ni (0.00 – 0.02 mgL) was below recommended values. Only Zn (0.54 – 18.07 mgL) was exceeded the ISI permissible limit for potable water in samples G2 G3. Overall findings indicated that groundwater bodies at residential area nearby major industrial areas of Jaipur city were good and to be used as potable water except samples G2 and G3.